Irrational Rationality of Individualism, Tortuous Logic of Collectivism, and Cardinal Stefan Wyszyński’s Integral-Humanist Concept of Socio-Political Life - Ryszard Ficek (Wrocławski Przegląd Teologiczny, 2021)
Stefan Wyszyński’s social thought can be defined as an integral-humanistic concept of sociopolitical life. This study, based on the analysis of source texts and studies using the historical and analytical method, examines the specificity of collectivism and individualism as two radically different attitudes in opposition to the personalistic and integral-humanistic conception of the human person presented by Cardinal Stefan Wyszyński, the Primate of Poland. The cardinal’s sociopolitical thoughts will be explored, reconstructed and reinterpreted with the employment of the inductive-deductive method. The interpretation of source materials will unravel the role and meaning of the personalistic view in the context of “incomplete” ideological concepts shaping the present reality of social and political life. Therefore, an essential goal of this study is to present the most critical components of the teaching and pastoral ministry of the Primate of the Millennium concerning collectivism and individualism. The author of the article raises a question whether the integral-humanistic concept of the human person and his involvement in the world as presented by Wyszyński can be applied to the specific realities of modern-day social life. The answer is significant, especially in the context of the contemporary reality of the Church, civil society, nation, and state.